Shortcuts for Electron‐Transfer through the Secondary Structure of Helical Oligo‐1, 2‐Naphthylenes. Issue 72 (9th December 2019) - Castrogiovanni, Alessandro; Herr, Patrick; Larsen, Christopher B.; Guo, Xingwei; Sparr, Christof; Wenger, Oliver S.
Abstract: Atropisomeric 1, 2‐naphthylene scaffolds provide access to donor–acceptor compounds with helical oligomer‐based bridges, and transient absorption studies revealed a highly unusual dependence of the electron‐transfer rate on oligomer length, which is due to their well‐defined secondary structure. Close noncovalent intramolecular contacts enable shortcuts for electron transfer that would otherwise have to occur over longer distances along covalent pathways, reminiscent of the behavior seen for certain proteins. The simplistic picture of tube‐like electron transfer can describe this superposition of different pathways including both the covalent helical backbone, as well as noncovalent contacts, contrasting the wire‐like behavior reported many times before for more conventional molecular bridges. The exquisite control over the molecular architecture, achievable with the configurationally stable and topologically defined 1, 2‐naphthylene‐based scaffolds, is of key importance for the tube‐like electron transfer behavior. Our insights are relevant for the emerging field of multidimensional electron transfer and for possible future applications in molecular electronics. Abstract : Taking shortcuts : Phototriggered electron transfer between a triarylamine unit and a ruthenium complex follows shortcuts in the secondary structure of a naphthylene‐based molecular bridge, leading to a particularly low distance dependence of reaction rates and overall faster electron transfer (see scheme).